Comparing Economic Management in Nonprofit Summer Camps : Insights from Germany and the Czech Republic - Kotačka, Hynek (2025)
This bachelor’s thesis examines the economic management practices of small-scale nonprofit summer camps in Germany and the Czech Republic through a comparative case of two organizations: Uni im Grünen e.V. and 5. PS Děčín. The camps, both situated near the German Czech border, were selected in order to minimize cultural and geographical differences while allowing for the comparison of distinct organizational structures. The thesis uses both quantitative and qualitative methods of analysis by analyzing financial data through the use of several financial metrics and comparing them with information gleaned from semi-structured interviews with camp managers of the respective camps. The study identifies key strengths, weaknesses and areas for improvement in areas such as budgeting, transparency, and revenue diversification. The findings reveal insights into the intricacies of summer camp management and their financial reporting, highlighting the challenges faced by volunteers running these small organizations. The insights provided by this thesis contribute to the academic understanding of nonprofit summer camp management and offer practical support for camps seeking to improve their efficiency and sustainability.